Development E-modul of History Learning Strategy to Improve Student Digital Literacy - Eva Dina Chairunisa1; Ahmad Zamhari (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2022)
Referring to the four competencies that must be possessed in the 21st century, digital literacy skills are one of the most important competencies for today's young generation especially student of history education. The problem of this research is how to develop an e-module in the History Learning Strategy course in History Study Program in Faculty of Teacher and Training Education, University of PGRI Palembang. The purpose of this research is to produce e-modules in the History Learning Strategy course. This study uses a development research method with stages, namely, need assessment, literature review, planning, developing the preminarry form of product, product revision, preminnary field test, and product revision. In this module, it is organized into five major sections, consisting of learning theory, PAIKEM, models, methods and learning media as well as examples and assessments of historical learning. The results showed that this e-module was considered communicative and user friendly to be used by students taking the History Learning Strategy course.